FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM: PERAN KINERJA PERUSAHAAN MAKANAN DAN MINUMAN DI INDONESIA - Ahmad Ahmad (Universitas La Tansa Mashiro, 2022)
The stock price is a description of the performance of a company. Basically, investors measure the performance of a company in managing its resources to generate profits. This study aims to determine the effect of book value per share and earnings per share on share prices, either partially or simultaneously, in food and beverage companies listed on the Indonesian stock exchange for the 2018-2020 period. The method used is descriptive analysis with a quantitative approach. The population is 30 companies and after selecting the sample using purposive sampling technique, 16 companies are obtained as samples. The type of research data is secondary data. The data analysis model of this research uses the prerequisite test of data analysis including: normality test, autocorrelation test, multicollinearity test, and heteroscedasticity test. The hypothesis test used includes: multiple linear regression analysis, correlation analysis, coefficient of determination, t test and f test. Based on the results of the correlation test, the BVPS value to the stock price is significant and EPS to the stock price is significant. The results of the determination test obtained a significant R Square value. The results of the t-test that have been carried out, the Book Value Per Share variable has no significant effect on stock prices. While the Earning Per Share variable has an effect on stock prices. In this study, together, Book Value Per Share and Earning Per Share have a significant effect on stock prices.